Tax incentives for industry in less developed countries - Heller, Jack.; Kauffman, Kenneth M. (Law School of Harvard University, Cambridge, 1963)
This book is the product of a three-year association, 1958 - 1961, between the authors and the Harvard Law School International Program in Taxation.
Includes bibliographical footnotes" (p. 196-275)
osc 10/12/2018
Loans
Keywords: Taxation; Tax exemption; Investments, American; Developing countries